Incidence, risk and protective factors of symptoms after colonoscopy. Issue 12 (December 2022) - Collatuzzo, Giulia; Boffetta, Paolo; Radaelli, Franco; Cadoni, Sergio; Hassan, Cesare; Frazzoni, Leonardo; Anderloni, Andrea; Laterza, Liboria; La Marca, Marina; Rogai, Francesca; Binda, Cecilia; Montale, Amedeo; et al.
Abstract: Background: Few studies focused on minor adverse events which may develop after colonoscopy. Aims: To investigate the incidence and factors associated to post-colonoscopy symptoms. Methods: This is a prospective study conducted in 10 Italian hospitals. The main outcome was a cumulative score combining 10 gastrointestinal (GI) symptoms occurring the week following colonoscopy. The analyses were conducted via multivariate logistic regression. Results: Of 793 subjects included in the analysis, 361 (45.5%) complained the new onset of at least one GI symptom after the exam; one symptom was reported by 202 (25.5%), two or more symptoms by 159 (20.1%). Newly developed symptoms more frequently reported were epigastric/abdominal bloating (32.2%), pain (17.3%), and dyspeptic symptoms (17.9%). Symptoms were associated with female sex (odds ratio [OR]=2.54), increasing number of symptoms developed during bowel preparation intake (OR=1.35) and somatic symptoms (OR=1.27). An inverse association was observed with better mood (OR=0.74). A high-risk profile was identified, represented by women with bad mood and somatic symptoms (OR=8.81). Conclusion: About half of the patients develop de novo GI symptoms following colonoscopy. Improving bowel preparation tolerability may reduce the incidence of post-colonoscopy symptoms, especially in more vulnerable patients.